1973
DOI: 10.1063/1.1654968
|View full text |Cite
|
Sign up to set email alerts
|

Bubble domains in magnetostatically coupled garnet films

Abstract: Bubble domains have been observed in five composite garnet structures consisting of two epitaxial magnetic layers separated by a layer of nonmagnetic garnet. The static and ``ordering'' properties of the domains are described and the arrangement of the overlying domains is discussed as a function of bias field. It is shown qualitatively that the strength of the magnetostatic interaction between the two magnetic layers can be changed considerably by varying the relative film thicknesses in the composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 2 publications
0
60
0
Order By: Relevance
“…Indeed, realization of magnetic skyrmions was recently discovered in polar magnet GaV 4 S 8 with rhombohedral C 3v symmetry [116]. In addition to these non-centrosymmetric ferromagnets, observations of skyrmions have been reported even for centrosymmetric ferromagnetic insulators with uniaxial anisotropy such as Y 3 Fe 5 O 12 [137,136] [140]. Crystal structures of these materials have spatial inversion symmetry, and thus the Dzyaloshinskii-Moriya interaction is not active.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Indeed, realization of magnetic skyrmions was recently discovered in polar magnet GaV 4 S 8 with rhombohedral C 3v symmetry [116]. In addition to these non-centrosymmetric ferromagnets, observations of skyrmions have been reported even for centrosymmetric ferromagnetic insulators with uniaxial anisotropy such as Y 3 Fe 5 O 12 [137,136] [140]. Crystal structures of these materials have spatial inversion symmetry, and thus the Dzyaloshinskii-Moriya interaction is not active.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…1 However, due to the manifold of interaction mechanisms between spins, the generation of skyrmions is not a trivial matter. [2][3][4][5][6][7][8][9][10][11][12] Spin spirals are also chiral spin textures, and are topologically similar to skyrmions. The close association between these spiral and skyrmion phases necessitates a careful and systematic study of the competing interaction mechanisms, especially the symmetric and antisymmetric exchange in the context of chiral states, and the rationale for their proclivity towards either spin texture in different material systems.…”
Section: Introductionmentioning
confidence: 99%
“…So far, they have been observed in materials with perpendicular magnetic anisotropy in connection with one of the following stabilization mechanisms: (i) four-spin exchange, leading to the formation of a Skyrmion lattice with each Skyrmion extending over a few lattice sites [2]; (ii) the Dzyaloshinskii-Moriya interaction [3,4], which is active in noncentrosymmetric helimagnets, where Skyrmions have typical dimensions of few tens of nanometers [5][6][7][8]; (iii) the long-range dipoledipole interaction (DDI) [9] stabilizing Skyrmions with a typical lateral size of the order of 1 m [10][11][12]. It has been recently found that the DDI can induce a larger and more complex variety of magnetic textures with respect to the ones that are observed in association with four-spin exchange and the Dzyaloshinskii-Moriya interaction [9].…”
mentioning
confidence: 99%